A new species of Metopeurum Mordvilko, 1914 (Hemiptera: Aphididae) from the Transcaucasus, with a key to the species of this genus - Barjadze, Shalva; Stepanyan, Ilona; Kalashian, Mark; Karagyan, Gayane; Gabrielyan, Ivan; Thieme, Thomas (Zootaxa, 2024)
The new aphid species Metopeurum caucasicum sp. nov. living on Achillea millefolium and five species of Tanacetum, namely T. abrotanifolium, T. balsamita, T. balsamitoides, T. canescens and T. vulgare (Asteraceae) in Armenia and Georgia, is described based on the apterous viviparous females. Diagnosis to other species of the genus is given. Some diagnostic characters of the holotype of Metopeurum capillatum (Börner, 1950), which was originally briefly described, are presented. An updated identification key for apterous viviparous females of all Metopeurum species is provided.